What does the possibility of a Freudian aesthetic theory entail? Contributions to History of Philosophy - Fasolino, Rubén C. (Revista de Filosofía, 2021)
This is an introduction to the possible implications of «Freudian aesthetics » which would be imbued by Freud’s unfinished project: The foundation of Trieblehre.